They, you, I: Fictionality and the Greenlandic suicide situation in Niviaq Korneliussen’s Blomsterdalen - Meyer, Pernille (Nordlit, 2024)
In this article, I analyse Niviaq Korneliussen’s treatment of the current Greenlandic suicide situation in the novel Flower Valley (Blomsterdalen, 2020). The novel is – according to the author – «political», which raises several questions: Why write a novel instead of an opinion piece? What possibilities does fiction open? In what ways can a novel contribute to discussing and nuancing political, cultural, and human issues? Drawing on rhetorical fictionality theory, I focus on Korneliussen’s use of local fictionality, particularly in the form of death representations, composition, and pronominal shifts, demonstrating how she, trough the novel’s countdown structure, for instance, presents perspectives that seem inaccessible outside literature.